Mengembangkan Kreativitas Dan Inovasi Peserta Didik Melalui Nilai-Nilai PAI - Abdul Majid; Abdul Solahudhin; Iswahyudi Iswahyudi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Innovation in Islamic Religious Education (PAI) learning is a strategic necessity in facing the dynamics of 21st-century education and supporting the achievement of the Sustainable Development Goals (SDGs), particularly SDG 4 on quality education and SDG 9 on innovation and technology. As Faizah (2023) emphasized, Islamic Religious Education (PAI) learning is no longer solely oriented toward knowledge transfer but must also be directed toward developing an innovative curriculum based on global ethics and sustainability. Furthermore, Anwar (2024) emphasized that the use of digital technology has been proven to enhance students' critical and creative thinking skills, particularly through the use of interactive media based on digital learning. This finding is reinforced by Yusuf (2024), who stated that teacher creativity is a dominant factor in ensuring active student engagement through collaborative and project-based learning models. In terms of implementation, Rahmawati's (2024) research shows that SDG-based learning innovations at the elementary school level have begun to be implemented through a contextual learning approach, although challenges remain regarding teachers' digital competencies. Meanwhile, a study by Wijaya (2025) showed that the project-based learning (PjBL) approach significantly improved students' creativity and problem-solving skills in Islamic Religious Education (PAI). Based on a literature synthesis, this study concluded that technology integration, innovative pedagogical approaches, and teacher competency are key factors in successfully transforming Islamic Religious Education (PAI) learning into a visionary, adaptive, and relevant learning environment for future needs. This study recommends improving teacher training, providing a digital learning ecosystem, and providing educational policies that support sustainable innovation.